Penerapan Asas Pemeriksaan Pengadilan Terbuka Untuk Umum Dalam Permohonan Uji Materiil di Mahkamah Agung - Lukmanul Hakim; Iwan Rachmad Soetijono; Al Khanif (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to find out and analyze related to the application of the foundations of open court examination of the substantive regulation of legislation in the Supreme Court, this writing uses the method of normative law research. The outcome of the writing explains that the provisions relating to the application of the principle of open court examination to the general public in the material examination at the Supreme Court are not regulated either in the Law No. 5 of 2004 amending the Act No. 14 of 1985 on the supreme court but abstractly the examination of the court open to the public is regulated in Article 13 of the Law on the Power of the Judiciary No. 48 of 2009. On the application of the basis of the examination of the court hearing open to the public is forced to open the hearing attended by the general public. When a judge's assembly is to open a hearing, it must declare that the hearing is open to the public.